Inverse Analysis in Civil Engineering: Applications to Identiﬁcation of Parameters and Design of Structural Material Using Mono or Multi-Objective Particle Swarm Optimization - Fontan, M.; Ndiaye, A.; Breysse, D.; Castéra, P. (IntechOpen, 2012)
None